Research, #Huh? Improving research awareness in NHS Grampian through a website and more. (22nd September 2020) - Berry, Emma; D'Alessandro, Mariella
Abstract : page_180 other Our public-facing website #Huh (Helping U Help) – www.grampianclinicalresearch.com – has been designed to engage public, patients and staff in clinical research. We have included views from patients and the public in its design and content, using multiple methods to gather feedback, some proving more successful than others. This article presents how our website was developed, including the different methods we used to gather views from the patients and public before, during and after its development. We hope that this paper will give useful insights to other people interested in incorporating stakeholder feedback into their own work.